The Geological Map of Mimas v1.0-2023 - Balázs Bradák; Motoharu Okumi (Geosciences, 2024)
A theory about a young, evolving “stealth ocean” under the ancient-looking surface of Mimas, the moon of Saturn, triggered us to revisit the icy satellite and develop a revised geological map based on Cassini images. The re-mapping of Mimas’s surface aimed to fill the decades-long gap that grew since the publication of the first Voyager image-based pioneering map, and it provided an up-to-date synthetic interpretation of revised and newly discovered features. Despite the map being in its early stage of introduction, it already showed some key features that may play significant roles in the reconstruction of Mimas’s (surface) evolution. The Herschel crater, formed by a global-scale impact, undoubtedly left additional marks, including fault scarps, stair-step faults, and post-impact surface transformation, through mass movements around the crater wall and the peak. Smaller craters left various scars on the surface, including asymmetric craters, whose morphology and allocation we used to reconstruct the regional topographic changes on the surface of Mimas. In addition to the impact-related features, which dominated the surface of the icy satellite, groups of weak, quasi-parallel running linear features, such as undifferentiated lineaments, grooves/through, and ridges, were also observed. The appearance and pattern of those lineaments overlapped with the allocation of various modeled global nonlinear tidal dissipations, supporting the existence of theoretical subsurface stealth oceans.